Symphonia i symphoniacus u Petroniusza – analiza semantyczna - Heintze, Michał Adam (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Heintze Michał Adam, Symphonia i symphoniacus u Petroniusza – analiza semantyczna (Symphonia and symphoniacus – semantic analysis in Petronius). In this article the author discusses the meaning of words „symphonia” and „symphoniacus” in the Satyricon of Petronius. The semantic analysis of the words is based on dictionaries and examples from latin literature.The most important dictionary for this paper was Lexicon totius Latinitatis of E. Forcellini. Even today this Lexicon is a very usefull philological tool.